Global Environmental Policy in the Context of Neo-liberal Capitalism (Hekima Review, 2015)
Why has global environmental policy been less forceful and less effective in helping tackle the problem of environmental degradation and the challenge of climate change? This paper argues that it is because current global environmental policy is grounded on an erroneous framing of the problem of environmental degradation. Neoliberal capitalism, as the dominant economic system, has largely been responsible for the ecological crisis facing the world, yet this fact is overlooked by global environmental policy, mainly because the theoretical underpinnings of global environmental policy are themselves provided by neoliberal capitalism. This creates an incompatibility with environmental sustainability.